An Analysis of Content Feasibility from BSNP on “Bahasa Inggris” Textbook for the XI Grade - Apta Vania Putri Triyanto; Lidiyatul Izzah (Scripta : English Department Journal, 2022)
Based on the 2013 curriculum, this study analyzes an English textbook for senior high school students in the XI grade entitled "Bahasa Inggris." The assessment used a BSNP rubric, which is in accordance with the 2013 curriculum's core and basic competencies. An explanation-heavy descriptive qualitative methodology is used in this investigation. Using the BSNP assessment criteria, the researcher modified the textbook material to match the core competencies and basic competencies of the 2013 curriculum. Data were obtained by the researcher using document analysis. Secondly, because the researcher focused on the subject in the first semester, only four chapters were analyzed. According to the study's findings, 53% of the content is proof of concept. This indicates that the content used for the XI grade in the "Bahasa Inggris" textbook during the first semester is still acceptable.